Effects of expanding and pelleting diets on finishing pigs fed from wet/dry feeders - N Amornthewaphat; Joe D Hancock; Keith C Behnke; Leland J McKinney; C W Starkey; D J Lee; C L Jones; J S Park; D W Dean (Kansas Agricultural Experiment Station Research Reports, 2000)
Pigs fed pelleted and expanded diets from wet/dry feeders had 4.4% greater ADG and 7.9 % greater efficiency of gain than pigs fed a mash diet. Also, trends for greater efficiencies of gain occurred among pigs fed expanded pellets vs standard pellets and expandate vs expanded pellets.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Expanding; Pelleting; Wet/Dry feeders; Finishing pigs